The Socio-Cultural Digital Innovation Capacity for Business Competitiveness of Traditional Craft SMEs in Makassar - Yulianto, Harry; Rohani, Rohani; Jumarti, Jumarti (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
Traditional craft Small and Medium Enterprises (SMEs) in Indonesia, particularly in Makassar, face an existential challenge in the digital era: balancing cultural preservation with the need to adopt digital technology for business competitiveness. This study aims to test the influence of the Socio-Cultural Digital Innovation Capacity (SCDIC), comprising Adaptive Digital Literacy (X1), Socio-Cultural Preservation (X2), and Collaborative Governance (X3), on the Business Competitiveness (Y) of these SMEs. Using a quantitative explanatory approach, data were collected through a survey of 350 respondents selected via stratified random sampling. Multiple linear regression analysis revealed all three SCDIC dimensions have a significant positive effect on business competitiveness, both partially and simultaneously. The model demonstrates strong predictive power, with an R-Square value of 0.75. Socio-Cultural Preservation was found to have the strongest influence (β=0.34), followed by Collaborative Governance (β=0.33) and Adaptive Digital Literacy (β=0.32). The study concludes an integrated approach, synergizing adaptive digital capabilities, socio-cultural preservation, and multi-stakeholder collaboration, is crucial for building sustainable competitive advantage for traditional craft SMEs in the digital transformation era.